Liraglutide after diet-induced weight loss for pain and weight control in knee osteoarthritis: a randomized controlled trial. Issue 2 (20th January 2021) - Gudbergsen, Henrik; Overgaard, Anders; Henriksen, Marius; Wæhrens, Eva Ejlersen; Bliddal, Henning; Christensen, Robin; Nielsen, Sabrina Mai; Boesen, Mikael; Knop, Filip Krag; Astrup, Arne; Rasmussen, Marianne Uggen; Bartholdy, Cecilie; et al.
ABSTRACT: Background: Weight loss is critical for preventing and managing obesity-related diseases. There is a notable lack of valid and reliable means to manage patients with overweight/obesity and knee osteoarthritis (KOA). Objective: To determine the efficacy and safety of liraglutide in a 30 mg/d dosing in patients with overweight/obesity and KOA. Methods: The trial was designed as a randomized controlled trial including patients between the age of 18 and 74 y with KOA and a BMI ≥27 (measured in kg/m 2 ). Patients underwent a pre–random assignment diet intervention (week –8 to 0). At week 0, patients having lost >5% of their body weight were randomly assigned to liraglutide 3 mg/d or placebo for 52 wk. The coprimary outcomes were changes in body weight and the Knee injury and Osteoarthritis Outcome Score (KOOS) pain subscale from week 0 to 52. Results: In total, 168 patients enrolled and 156 were randomly assigned to receive liraglutide or placebo. Patients experienced a significant reduction in body weight and KOOS pain during the pre–random assignment dietary intervention period (week −8 to 0). From week 0 to 52 there was a significant difference in body weight between the liraglutide and placebo group (mean changes: −2.8 and +1.2 kg, respectively; group difference, 3.9 kg; 95% CI: −6.9, −1.0; P = 0.008). There was, however, no group difference in KOOS pain (mean changes: 0.4 and –0.6 points, respectively; group difference, 0.9 points; 95% CI: −3.9, 5.7; P = 0.71). Treatment-emergent adverse events related to the gastrointestinal system were experienced by 50.2% and 39.2% of patients in the liraglutide and placebo groups, respectively. Conclusions: In patients with KOA and overweight/obesity liraglutide added after an 8-wk pre–random assignment diet induced a significant weight loss at >52 wk but did not reduce knee pain compared to placebo. This trial was registered at clinicaltrials.gov as NCT02905864.